Inauguración del módulo de tutoría telefónica. (UNED, 2023)
De izquierda a derecha: Walter Sagot Castro, Rodrigo Gámez Lobo, Chester Zelaya Goodman, Ronald García Soto - Vicerrector Ejecutivo, Eugenio Rodríguez Vega- Consejo Editorial, Federico Vargas, Jorge Múncia, Jorge E. Guillen, Marco Vinicio Álvarez Amador - Vicerrector de Planificación, Elmer Acevedo Sánchez